2021
DOI: 10.1002/path.5643
|View full text |Cite
|
Sign up to set email alerts
|

Dual proteotoxic stress accelerates liver injury via activation of p62‐Nrf2

Abstract: Protein accumulation is the hallmark of various neuronal, muscular, and other human disorders. It is also often seen in the liver as a major protein‐secretory organ. For example, aggregation of mutated alpha1‐antitrypsin (AAT), referred to as PiZ, is a characteristic feature of AAT deficiency, whereas retention of hepatitis B surface protein (HBs) is found in chronic hepatitis B (CHB) infection. We investigated the interaction of both proteotoxic stresses in humans and mice. Animals overexpressing both PiZ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…32 Finally, the mouse model was instrumental to investigate the role of cofactors in the modulation of liver disease. In that respect, overexpression of hepatitis B surface protein, as seen in individuals with chronic hepatitis B infection, was found to aggravate liver injury, fibrosis, and the frequency of hepatocellular carcinoma in Pi*Z mice, 33 while the mild iron accumulation seen in homeostatic iron regulator (Hfe) gene knockout animals did not have a significant effect. 34 Notably, administration of the nonsteroidal anti-inflammatory drug indomethacin increased liver damage via activation of the IL-6-STAT-3 pathway in Pi*Z mice.…”
Section: Mechanisms Of Aatd-related Liver Injurymentioning
confidence: 99%
“…32 Finally, the mouse model was instrumental to investigate the role of cofactors in the modulation of liver disease. In that respect, overexpression of hepatitis B surface protein, as seen in individuals with chronic hepatitis B infection, was found to aggravate liver injury, fibrosis, and the frequency of hepatocellular carcinoma in Pi*Z mice, 33 while the mild iron accumulation seen in homeostatic iron regulator (Hfe) gene knockout animals did not have a significant effect. 34 Notably, administration of the nonsteroidal anti-inflammatory drug indomethacin increased liver damage via activation of the IL-6-STAT-3 pathway in Pi*Z mice.…”
Section: Mechanisms Of Aatd-related Liver Injurymentioning
confidence: 99%
“…Serum proteins are produced in the ER before being secreted into the bloodstream through the Golgi apparatus. A large network of chaperones, foldases, and cofactors, such as the calnexin–calreticulin system and binding immunoglobulin protein, are responsible for facilitating protein folding and quality control in the ER 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…A large network of chaperones, foldases, and cofactors, such as the calnexin-calreticulin system and binding immunoglobulin protein, are responsible for facilitating protein folding and quality control in the ER. [29,30] Accumulation of abnormal proteins leads to ER stress, which engages the "unfolded protein response". Irreversible ER stress results in the apoptosis of damaged cells through various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation of autophagy has been associated with several liver diseases and its regulation has been recognized as a potential novel treatment strategy (39). However, the results of studies investigating the effects of autophagy on liver fibrosis or cirrhosis are contradictory (40)(41)(42)(43)(44). A number of studies have suggested that autophagy prevents the development of liver fibrosis (41,44).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that autophagy prevents the development of liver fibrosis (41,44). On the other hand, other studies have demonstrated that autophagy promotes the progression of hepatic fibrosis (42,43). The aforementioned studies suggested that autophagy could regulate multiple biological processes that affect the onset hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%